New paradigm of digital marketing in emerging markets: from social media to social customer relationship management. (2016) - Alavi, Shirin
The purpose of this paper is to explore the usage of Facebook as one of the biggest tools in the promotion of Social Customer Relationship Management. In the last few years, the organisations in the emerging markets like India have witnessed an explosive growth in the tactic and process of building quality social and professional networks and further leveraging them for customer retention and achieving the goals of Social CRM, namely social engagement and social collaboration. Facebook is the most popular social media. It figures out the niche and with proper investment of time and resources via tools and technology provides its customers the best service. It has come out to be one of the biggest tools in promotion of Social CRM. This research paper would primarily focus on the Social CRM strategies adopted by Facebook for improving the organisation-customer interfaces, which also serve as a persuasive technology in business.